The hydration status and thyroid hormones levels among elite wrestlers. Dehydration-induced thyroid hormones - Yagmur, R.; Isik, O.; Kilic, Y.; Akyuz, M. (Progress in Nutrition, 2019)
Study Objectives: Dehydration causes various loss of physical and physiological functions and also thyroid hormones are important for maintaining the normal physiological function of the body and regulate basic metabolism in the human body. The aim of this study was to examine the effect of pre-competition dehydration on elite wrestlers` thyroid hormones levels. Sixty-nine elite wrestlers participated in the study. Methods: The retrospective research model was used in the study. In previously obtained blood samples were determined Sodium (Na+), Blood Urea Nitrogen (BUN), Glucose, Potassium (K), Triiodothyronine (T3), Thyroxine (T4) and Thyroid Stimulating Hormone (TSH) levels. The wrestlers Posm levels were calculated using a mathematical formula and Posm levels >290 who wrestlers as the dehydration group and Posm levels =290 who wrestlers as the euhydration group were divided into two groups. The Kolmogorov-Smirnov test was used for the normality test of the data. The independent samples t-test was used in the analysis of the obtained data. Significance was set at 0.05. Results: According to the results of this study, it was determined that ~45% of pre-competition wrestlers were exposed to dehydration. When the dehydration and euhydration groups were compared, there was a significant difference in BUN and Na+ levels as the hydration markers and there was no difference in Glucose and K levels. When the difference between thyroid hormones levels was examined, it was found that there was a statistical difference between T3 levels and there was no difference between T4 and TSH levels. Conclusion: T3 levels of elite wrestlers were lower in dehydration group than the euhydration group, whereas T4 and TSH levels were not different between both groups.